71‐2: Invited Paper: Printed Transistors and MEMS for Large‐Area Electronics. Issue 1 (May 2016) - Subramanian, Vivek; Chung, Seungjun; Grau, Gerd; Scheideler, William J.
Abstract : Printing is a promising process technology for realization of lowcost, large area, and flexible electronic systems. To realize printed electronics, it is necessary to develop technologies for fabrication of printed devices such as transistors, etc., including development of the requisite printable materials, the underlying printing process technologies, and the integration strategies for fabrication of printed devices. This paper reviews our development of a wide range of printed switching devices, including printed organic transistors, printed inorganic transistors based on transparent oxides, and printed microelectromechanical switches.